BIOLOGY AND FISHERY OF ’CHOO PARAI’â€” SELAROIDES LEPTOLEPIS (CUVIER AND VALENCIENNES) Part II. Biology and Fishery - Tandon, K K (Indian Journal of Fisheries, 2011)
THE present account, dealing with the biology and fishery, forms the secondpart in the series on the study of Selaroides leptolepis. Details regardingthe material which formed the basis of this work have already been given inthe earlier paper (Tandon, 1960).